If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2a + -6) = 36 Reorder the terms: 3(-6 + 2a) = 36 (-6 * 3 + 2a * 3) = 36 (-18 + 6a) = 36 Solving -18 + 6a = 36 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 6a = 36 + 18 Combine like terms: -18 + 18 = 0 0 + 6a = 36 + 18 6a = 36 + 18 Combine like terms: 36 + 18 = 54 6a = 54 Divide each side by '6'. a = 9 Simplifying a = 9
| 8x-4=2x-5 | | x^2+4y^2-4x-8y-92=0 | | 3(2x-4)-8(x-7)=6x-8-8x | | 5y=3y-8 | | X+7=x+7*5 | | 1a+18=79 | | 6y+5=10+5y | | -x^3-x^2+2x=0 | | (2*-1)-3= | | 3(3)+3s=21 | | 16x+2y=25 | | (9x-24)=(6x-5) | | 3-6(-8+2x)=3(1-5x) | | 3x+8=9x+26 | | 2a+3a-3=17 | | C^2+8c+48= | | b^2-8b-16=0 | | 7+5+(2x-3)= | | 3x+4x-9=12 | | x+6x-78=97 | | 8t^2-56t+80=0 | | 2x+4=2x+x+3 | | x-31/4=21/5 | | 2x^3+3x^3+(-6x^3)= | | 2x^2-x=100 | | (2x+110)+2x=300 | | 1/2y≤-7 | | 10x^3-1250=0 | | (x-4)(x-3)(x-2+3i)(x+2+3i)=0 | | 2(2x+110)+2x=300 | | 2(x+3)+5x= | | 2y=-7x+12 |